2018
DOI: 10.1111/jocn.14007
|View full text |Cite
|
Sign up to set email alerts
|

Nonpharmacological approaches for behavioural and psychological symptoms of dementia in older adults: A systematic review of reviews

Abstract: There is a need for nurses to be informed of best practices in order to effectively plan appropriate interventions to address behaviours in older adults with dementia. Care planning and tailored, sensory-focused, nonpharmacologic approaches are safe and effective options for nurses to consider in practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
50
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 25 publications
(93 reference statements)
0
50
0
2
Order By: Relevance
“…Momentarily, different pharmacological and non-pharmacological therapies are recommended to reduce the frequency and severity of BPSD, that have been shown to be effective in slowing down the impairment, especially with regard to the cognitive symptoms that are inherent to dementia [14]. In general, non-pharmacological interventions are considered as a preferable alternative to pharmacotherapy, mainly because of the adverse effects that are found in pharmacological therapies [15,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Momentarily, different pharmacological and non-pharmacological therapies are recommended to reduce the frequency and severity of BPSD, that have been shown to be effective in slowing down the impairment, especially with regard to the cognitive symptoms that are inherent to dementia [14]. In general, non-pharmacological interventions are considered as a preferable alternative to pharmacotherapy, mainly because of the adverse effects that are found in pharmacological therapies [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The American Psychiatric Association [17] distinguishes non-pharmacological therapies that are conducted to treat dementia into four different categories: (1) cognition-oriented treatments (e.g., reality orientation, skills training), (2) emotion-oriented treatments (e.g., supportive therapy, validation/integrated emotion-oriented care, Snoezelen, reminiscence), (3) behaviororiented treatments (behavior therapy), and (4) stimulation-oriented treatments (e.g., activity or recreational therapy, art therapy, music therapy, exercise, psychomotor therapy). There is conflicting evidence with regard to the effectiveness of non-pharmacological interventions to improve BPSD [14], which makes it necessary to have a clear overview of the existing evidence.…”
Section: Introductionmentioning
confidence: 99%
“…Existing pharmacological options in NPS treatment include atypical antipsychotics, benzodiazepines, and other drugs (eg, mood stabilizers), which may, however, increase the risk of cognitive decline, cerebrovascular events, or mortality . Differently, systematic reviews have demonstrated the effectiveness of nonpharmacological treatments (NPTs) for NPS as well as the increase in perceived quality of life in PwD and their caregivers . Consequently, the National Institute for Health and Care Excellence dementia guidelines recommend NPTs as first‐line treatments in the management of noncognitive behavioral disturbances in PwD.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] Differently, systematic reviews have demonstrated the effectiveness of nonpharmacological treatments (NPTs) for NPS as well as the increase in perceived quality of life in PwD and their caregivers. 14,[18][19][20] Consequently, the National Institute for Health and Care Excellence dementia guidelines 21 focused on NPTs such as cognitive stimulation, pet therapy, doll therapy, and caregiver training in problem solving 18,22,23 to reduce NPS.…”
Section: Introductionmentioning
confidence: 99%
“…Further, a number of studies have demonstrated the benefits of nonpharmacological interventions on behavioural and psychological symptoms of dementia (BPSD; Legere et al . ; Logsdon et al . ; Scales et al .…”
Section: Introductionmentioning
confidence: 99%